(untitled) (Fiep Bulletin - online, 2014)
This work describes the direct punch biomechanics, verifying the influence of the rotation of the body in the transverse plan in the performance of this technique on a fixed target. This research had 10 practitioners of martial arts, with 15,3±10,5 years of experience, and 9 inexperienced individuals in fights. In these two groups the age average was 30 years and 78 the average corporal mass in kg. The collection of data was carried through with a force platform that served of target and measured the force of reaction of the punches. Also a camcorder (30Hz) located in the transverse plan of the executants of the punches was used and, through the pictures of image of this camera had been surveyed the angles of biacromial corporal displacement in the transverse plan. Each participant executed 4 direct punches on the fixed platform of force. Between the executed punches, the forces of reaction with the target of bigger magnitude, normalized for the corporal weight, were related with the biggest angular displacements of the body in the transverse plan. With this it was verified that the corporal displacement in the transverse plan is presented as a determinative biomechanics variable in the performance of direct punch.